Effects of complex coastal topography on overland tsunami flows - Gunasekaran, Dhinoharan (2014)
This report analyses the characteristics of a tsunami propagating up a composite slope and into tunnel like structures. Solitary waves are used to model the tsunami. Parameters such as the water depth, incident wave height and distance from shoreline were varied to observe changes and further understand tsunamis. The pressure profile in the tunnel was also studied.